Sedation versus general anaesthesia in endovascular therapy for anterior circulation acute ischaemic stroke: the multicentre randomised controlled AMETIS trial study protocol. Issue 9 (13th September 2019) - Chabanne, Russell; Fernandez-Canal, Charlotte; Degos, Vincent; Lukaszewicz, Anne-Claire; Velly, Lionel; Mrozek, Segolene; Perrigault, Pierre-François; Molliex, Serge; Tavernier, Benoit; Dahyot-Fizelier, Claire; Verdonk, Franck; Caumon, Elodie; et al.
Abstract : Introduction: Endovascular thrombectomy is the standard of care for anterior circulation acute ischaemic stroke (AIS) secondary to emergent large vessel occlusion in patients who qualify. General anaesthesia (GA) or conscious sedation (CS) is usually required to ensure patient comfort and avoid agitation and movement during thrombectomy. However, the question of whether the use of GA or CS might influence functional outcome remains debated. Indeed, conflicting results exist between observational studies with better outcomes associated with CS and small monocentric randomised controlled trials favouring GA. Therefore, we aim to evaluate the effect of CS versus GA on functional outcome and periprocedural complications in endovascular mechanical thrombectomy for anterior circulation AIS. Methods and analysis: Anesthesia Management in Endovascular Therapy for Ischemic Stroke (AMETIS) trial is an investigator initiated, multicentre, prospective, randomised controlled, two-arm trial. AMETIS trial will randomise 270 patients with anterior circulation AIS in a 1:1 ratio, stratified by centre, National Institutes of Health Stroke Scale (≤15 or >15) and association of intravenous thrombolysis or not to receive either CS or GA. The primary outcome is a composite of functional independence at 3 months and absence of perioperative complication occurring by day 7 after endovascular therapy for anterior circulation AIS. Functional independence is defined as a modified Rankin Scale score of 0–2 by day 90. Perioperative complications are defined as intervention-associated arterial perforation or dissection, pneumonia or myocardial infarction or cardiogenic acute pulmonary oedema or malignant stroke evolution occurring by day 7. Ethics and dissemination: The AMETIS trial was approved by an independent ethics committee. Study began in august 2017. Results will be published in an international peer-reviewed medical journal. Trial registration number: NCT03229148 .